Surgery of the Aortic Valve Using a Minimally Invasive Approach - Babliak, Oleksandr D.; Babliak, Dmytro Ye.; Yatsuk, Serhii V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. The aim of this study is to present and analyze the technique of isolated aortic valve replacement (AVR) or repair via a minimally invasive approach – right anterior thoracotomy in the second intercostal space. Materials and Methods. From February 2020 to November 2025, 180 patients at our institution underwent isolated aortic valve interventions. Since July 2020, we have implemented the technique of minimally invasive aortic valve surgery via right anterior thoracotomy. Between 2020 and 2025, 177 patients were operated on using this approach: 165 underwent aortic valve replacement (AVR), and 12 underwent aortic valve repair. In 2 (1.1 %) patients with isolated aortic valve stenosis, AVR was performed through axillary access for a better cosmetic effect. Since the introduction of this technique, median sternotomy was used in only one case due to difficulties with peripheral cannulation or severe aortic calcification. Results. Based on etiology and anatomical pathology, AVR was performed in 165 (91.6 %) patients – 90 (54.5 %) received biological prostheses, and 75 (45.5 %) received mechanical valves. Aortic valve repair was performed in 12 (8.4 %) patients. Aortic cross-clamp time ranged from 39 to 145 minutes (mean 89.4±19.5 min). Total cardiopulmonary bypass time ranged from 83 to 275 minutes (mean 150.9±29.4 min). Total operative time ranged from 165 to 435 minutes (mean 237.7±43.4 min). Intensive care unit (ICU) stay was 1.4±0.6 (1-3) days, and total hospital stay was 6.1±1.6 (3-16) days. There were no significant postoperative cardiac complications, mortality, or conversions to median sternotomy. Three cases (1.4 %) required surgical re-exploration due to bleeding. Conclusions. Right anterior mini-thoracotomy is a safe approach for aortic valve surgery. The use of exposure maneuvers during aortic valve replacement via mini-thoracotomy allows the operation to be performed without patient selection and yields good perioperative results.